Students Difficulties Using Webtoon Applications in Teaching Writing Skills: at Eight Grade SMPN 1 Klampis - Karimatul Millah; Mariyatul Kiptiyah; Tera Athena (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
This study aims to identify the difficulties experienced by grade VIII students in using webtoon apps to teach writing skills, as well as formulate effective learning strategies to overcome these difficulties. Qualitative research methodology was used, utilizing interviews, observations, and surveys to gather detailed insights from students at SMPN 1 Klampis. The results showed that students enjoy Webtoon apps but often experience difficulties such as generating ideas and organizing their writing effectively. Many students expressed feelings of frustration and anxiety when faced with writing tasks, which affected their overall motivation. These findings highlight the need for instructional strategies that can address these specific challenges. In conclusion, although Webtoon apps have the potential to improve writing skills, targeted support is essential to overcome the identified difficulties. Recommendations include providing structured guidance and focused writing exercises. In addition, training for teachers on how to effectively implement Webtoon in the classroom could further assist students in overcoming their writing challenges.